Evaluasi Efektivitas Pelatihan Peningkatan Mutu & Keselamatan Pasien (PMKP) di Rumah Sakit Universitas Indonesia - Gunawan, Susilawati; Shelladien Andrina, Kafa; Suhaeri, Muhammad (LPPM Universitas Respati Indonesia, 2025)
Education and training is a learning process to improve the competence and performance of hospital staff. Programme evaluation is a crucial aspect of human resource development (HRD) in the health sector and an integral part of continuous efforts to improve quality of health care and has an important role in ensuring the effectiveness, efficiency, and relevance of the programmes as well as helping to ensure that health personnel have knowledge, skills, and attitudes in line with established standards, also contributing to the improvement of patient safety. The aim of this research is to explore empirically the evaluation of training culture improvement of quality & safety of patients & 5R culture in the University of Indonesia Hospital, to know the training evaluation at the level of reaction, learning, behavior and results. The method used by the Kirkpatrick evaluation model with the type of research mix (quantitative-qualitative) in the Diklat Installation period 11 December 2023 – 10 January 2024. Evaluation of reaction levels using secondary data from RSUI survey results to evaluate sources, facilities, training success. Data collection is done by means of observation, in-depth interviews and documentation. The results obtained from the RSUI training course are good with good delivery quality (66%), good facilities (87%), good delivery success 89%, high reaction satisfaction of participants 83%, participant presence far from target. Evaluation of learning level is good with passing post test 97%. Behavior level evaluation requires organizational support, working environment and instructive motivation to change behavior. Training recommendations using blended learning devices/e-learning attempts to overcome low attendance, conduct pre-training tests and are interactive.